Learning Quantum Physics: An Effort to Overcome the Difficulties of Changing Concepts in Atomic Model Materials - Putra, F.; Mardova, L. (Procedia of Social Sciences and Humanities, 2024)
The study of quantum physics becomes more difficult because of the concept of classical physics that has been firmly embedded in the student's cognitive system. The material of the atomic model is one of the key materials in understanding quantum physics where there is a paradigm of thinking from classical physics to quantum physics. This study aims to produce step of atomic model learning to form the concept of quantum physics is right on students through literature analysis method. Questions about the cognitive theory of concepts become the main reference in the design of the steps (syntax) of learning the atomic model.